Maxillary Sinus Retention Cysts Protruding Into the Inferior Meatus - Sung-Lyong Hong; Kyu-Sup Cho; Hwan-Jung Roh (Clinical and Experimental Otorhinolaryngology, 2014)
Although most of the maxillary sinus retention cysts are asymptomatic, a few of them increase in size and cause symptoms. However, they rarely erode bony walls nor protrude into the inferior meatus. I present 2 cases with maxillary sinus retention cysts protruding into the inferior meatus by making a large defect on the medial wall of the maxillary sinus.